Practical approaches to collections care - Forsko, Samantha (Abingdon, Oxon ; New York, NY : Routledge ; Taylor & Francis, 2023)
"While cultural heritage practitioners and caretakers are often intimidated by "best practices", Practical Approaches to Collections Care helps to alleviate those concerns, offering a stepped approach to preservation encompassing a variety of collections care programs. The author, drawing on over a decade of experience working in libraries, museums, archives, and other historic sites, and specifically building off of her work as a Preservation Specialist at the Conservation Center for Art & Historic Artifacts, discusses realistic, efficient, and sustainable approaches to collection housing, space planning, environmental management, facilities care, emergency preparedness and much more. Giving examples of implementation and easy-to-follow guides that will allow readers to start from scratch or improve an already existing program, Forsko demonstrates how preservation can become a component of any collections care program. Encouraging the reader to start by taking small, manageable steps, the author shows that even the smallest of actions can make a difference that will ultimately help to preserve collections and ensure that the world's heritage will remain intact for future generations. Practical Approaches to Collections Care takes an applied approach, making suggestions the reader can immediately implement no matter the size of their institution. It is an essential tool for stewards of cultural heritage collections, particularly collections managers, registrars, and preservation specialists. It will also be useful to students who are engaged in the study of collections care"--
Introduction -- Intellectual control -- Storage enclosures and artifact housing -- Space planning and management -- Collections care in exhibitions -- Environmental management -- Facilities management -- Emergency preparedness and response -- Polices, plans, and procedures -- Conclusion.
Includes bibliographical references and index.
in English.
Keywords: Museum conservation methods; Museum -- Management; Museum -- Methods and techniques